2022
DOI: 10.1080/01434632.2022.2126487
|View full text |Cite
|
Sign up to set email alerts
|

The impact of foreign accent on irony and its consequences on social interaction

Abstract: Literature has shown that foreign-accented (FA) speech modulates the degree of irony perceived by native (NA) individuals, but the subsequent consequences it may have on social interaction are unknown. To address this question, we presented Spanish first language (L1) users with written contexts with ironic/literal praises allocated to either a NA or a FA speaker. Written modality was used to avoid disfluency and to examine the impact of expectations of non-L1 comprehension on irony processing. For each of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(102 reference statements)
1
3
0
Order By: Relevance
“…Also, the results indicated that words (independently of their valence) elicited overall higher arousal when processed in a native accent than when processed in a foreign accent. Our results extend and confirm previous findings that suggested an impact of the foreign accent on emotionality (Hatzidaki et al, 2015;Bazzi et al, 2022a). This reduction of the emotional response when stimuli are produced in a foreign accent can be attributed to several factors, which are not mutually exclusive, mainly, linguistic fluency, language attitudes, and the linguistic context of language acquisition, as developed in the following sections.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Also, the results indicated that words (independently of their valence) elicited overall higher arousal when processed in a native accent than when processed in a foreign accent. Our results extend and confirm previous findings that suggested an impact of the foreign accent on emotionality (Hatzidaki et al, 2015;Bazzi et al, 2022a). This reduction of the emotional response when stimuli are produced in a foreign accent can be attributed to several factors, which are not mutually exclusive, mainly, linguistic fluency, language attitudes, and the linguistic context of language acquisition, as developed in the following sections.…”
Section: Discussionsupporting
confidence: 92%
“…The fact that a speaker does not belong to the same social/linguistic group generates psychological distance, which may alter how the information coming from this speaker is processed and may lead to a more abstract perception of the reality (Liberman and Trope, 2008). In this line, in Bazzi et al (2022a) study reported in the Introduction, the origin of the speaker affected the emotionality elicited when processing social norms. Indeed, recall that the foreign accent associated with a negative stereotype (Moroccan) provoked a less intense emotional response compared to the native accent and unfamiliar foreign accent (Indonesian).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations